P03 Identification of intervention opportunities through assessment of the appropriateness of antibiotic prescribing in surgical patients in a UK hospital using a national audit tool: a single centre retrospective audit. (19th January 2023) - Hearsey, D; Bamford, K; Hutton, M; Wade, L; Coates, H; Ramsay, E; Alberts, B A; Powell, N
Abstract: Background: Identifying opportunities to safely reduce antibiotic prescribing is necessary for prescribers and antibiotic stewardship teams to minimize unwarranted antibiotic use. We aimed to quantify excess antibiotic use in General Surgery. Methods: We retrospectively audited the antibiotic prescribing for patients discharged from the General Surgery specialty in an acute hospital in the south-west of England between 01/08/21 and 31/08/21 using an audit tool developed by Public Health England. The appropriateness of prescribing was determined for each patient at three antibiotic decision time-points: at initiation, the pre-72h antibiotic review, and treatment duration. Two infection specialists and a general surgeon reviewed each patient. Indication and excess days of therapy (DOTs) were calculated at each decision time-point and expressed as a proportion of total DOTs. Results: Eighty-six patients were prescribed 1162 DOTs; 192 (16.5%) excess DOTs were prescribed in 38 patients (44%), with zero excess days identified in the remaining 48 patients (56%). Seventy-five of 192 (39%) excess DOTs occurred at initiation; 55/192 (29%) after the pre-72hour antibiotic review; and 62/192 (32%) due to protracted antibiotic courses. There was concordance between the general surgeon and infection specialist for the majority of apportioned excess DOTs. However, the surgeon apportioned fewer excess DOTs 160/1162 (13.8%). Overall IV antibiotics accounted for 53.4% of total DOTs. Seventy-two of 86 (83.7%) patients received 620 intravenous DOTs; of these, 79 (12.7%) IV DOTS were unnecessary. Conclusions: We have identified excess antibiotic prescribing in General surgery with comparable excess DOTs at all three time-points.